(untitled) (Journal of Informatics Education and Research, 2025)
The transition from full-time employment to retirement displays many challenges and opportunities. Many retirees face problems related to financial independence and also face difficulty in upholding of sense of purpose after retirement. In connection of this, a new path of Hobby-Driven Entrepreneurship is arising for retirees to transform their passions into income-generating ventures. This Hobby-Driven Entrepreneurship not only generates income source for them but also engage them in socially and personally in their post-retirement lives. This study outlines the important factors that influence retirees’ verdicts to promote their hobbies as commercial manner. These types of ventures initiatives demonstrate many challenges as they encounter in sustaining these enterprises. Income generation through these ventures remain a significant motivator for retirees that support themselves financially and on rising healthcare costs and living expenses. It is also observed that retirees non-financial initiatives using their hobbies for engaging their time offer them personal satisfaction, cognitive engagement, and social interaction. Later, this non-financial imitative somehow comes as driving force toward entrepreneurship. The world is changing with increasing accessibility of technology that continues facilitating the hobby-driven entrepreneurship. Retirees are using the digital platforms for marketing, sales, and networking. Using these online platforms, retirees are actively engaging in diverse business ventures like online business, selling their own handicraft online. However, there are many barriers observed such as digital literacy, market competition, and financial management challenges hinder their long-term success. This research emphasizes on the impact of hobby-based entrepreneurship on retirees’ like financial independence, cognitive health, and overall quality of life. The findings from this study provide useful insights to policymakers, financial planners, and retirees. This study outlines them for formulation of strategies to create successful and sustainable businesses. This study also encourages retirees to adopt hobby-based businesses that improve retirees’ financial security, mental health, and social connections, leading to a better quality of life in their later years.